CircINSR Regulates Fetal Bovine Muscle and Fat Development - Shen, Xuemei; Tang, Jia; Ru, Wenxiu; Zhang, Xiaoyan; Huang, Yongzhen; Lei, Chuzhao; Cao, Hui; Lan, Xianyong; Chen, Hong (Frontiers in Cell and Developmental Biology, 2021)
The level of muscle development in livestock directly affects the production efficiency of livestock, and the contents of intramuscular fat (IMF) is an important factor that affects meat quality. However, the molecular mechanisms through which circular RNA (circRNA) affects muscle and IMF development remains largely unknown. In this study, we isolated myoblasts and intramuscular preadipocytes from fetal bovine skeletal muscle. Oil Red O and BODIPY staining were used to identify lipid droplets in preadipocytes, and anti-myosin heavy chain (MyHC) immunofluorescence was used to identify myotubes differentiated from myoblasts. Bioinformatics, a dual-fluorescence reporter system, RNA pull-down, and RNA-binding protein immunoprecipitation were used to determine the interactions between circINSR and the micro RNA (miR)-15/16 family. Molecular and biochemical assays were used to confirm the roles played by circINSR in myoblasts and intramuscular preadipocytes. We found that isolated myoblasts and preadipocytes were able to differentiate normally. CircINSR was found to serve as a sponge for the miR-15/16 family, which targets CCND1 and Bcl-2. CircINSR overexpression significantly promoted myoblast and preadipocyte proliferation and inhibited cell apoptosis. In addition, circINSR inhibited preadipocyte adipogenesis by alleviating the inhibition of miR-15/16 against the target genes FOXO1 and EPT1. Taken together, our study demonstrated that circINSR serves as a regulator of embryonic muscle and IMF development.